Pelatihan Media Pembelajaran Berbasis Komik bagi Guru SD di Wilayah Kabupaten Tasikmalaya - Puji Lestari; Nani Ratnaningsih; Diar Veni Rahayu; Khomsatun Ni’mah (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
With the government program related to the provision of IT facilities and infrastructure in schools in the Tasikmalaya Regency area, it is challenging for teachers to be able to use them optimally. However, their knowledge and skills regarding the use of interactive learning media are still limited. Thus, the service regarding training and mentoring of learning media is deemed necessary to improve the competence of elementary school teachers in the Tasikmalaya Regency area. The description of the implementation of training and assistance in the use of comic-based interactive learning media consists of: (1) training on the use of comics as a learning medium for elementary school-aged children that focuses on numeracy literacy and reading literacy; (2) assistance in designing comic-based learning media for elementary school-aged children using storyboardthat.com. (3) improving teacher skills in implementing learning for elementary school-aged children through comic-based learning. The output targets that will result from the implementation of this regional scheme service (PbM-KW), are publications in national journals, and online media/local newspapers.